Temporal trends in cardiovascular disease risk factor profiles in a population-based schizophrenia sample: a repeat cross-sectional study. Issue 1 (23rd October 2017) - Chiu, Maria; Rahman, Farah; Vigod, Simone; Wilton, Andrew S; Kurdyak, Paul
Abstract : Background: People with schizophrenia have an increased burden of cardiovascular diseases (CVD); however, little is known about the cardiovascular risk factor profiles of non-institutionalised individuals with schizophrenia. This study estimated the prevalence of CVD risk factors in a population-based sample of Canadians with and without schizophrenia. Methods: Ontario respondents of the Canadian Community Health Survey were linked to administrative health databases; using a validated algorithm, we identified 1103 non-institutionalised individuals with schizophrenia and 156 376 without schizophrenia. We examined the prevalence of eight CVD risk factors: smoking, diabetes, hypertension, obesity, physical inactivity, fruit/vegetables consumption, psychosocial stress and binge drinking. To examine temporal trends, we compared prevalence estimates from 2001–2005 to 2007–2010. Results: The prevalence of most CVD risk factors was significantly higher among those with schizophrenia than the general population. Obesity and diabetes prevalence increased by 39% and 71%, respectively, in the schizophrenia group vs 11% and 24%, respectively, in the non-schizophrenia group between the two time periods. Unlike the general population, smoking rates among those with schizophrenia did not decline. Almost 90% of individuals with schizophrenia had at least one CVD risk factor and almost 40% had ≥3 co-occurring risk factors. Conclusion: Individuals with schizophrenia had a greater prevalence of individual and multiple CVD risk factors compared with those without schizophrenia, which persisted over time. Our findings suggest that public health efforts to reduce the burden of CVD risk factors have not been as effective in the schizophrenia population, thus highlighting the need for more targeted interventions and prevention strategies.